Hesitatif sebagai Pelengkap Jenis Tindak Tutur Ilokusi Menurut Searle - Yustinus Budi Setyanta (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
The goal of this study is expressing teacher’s speech acts in academic interaction at Indonesian class in Wisma Bahasa Yogyakarta. This study used qualitative approach in pragmatics aspect. The data collection that used in this study is nonparticipative observation with record and written technic. In this method two research subjects that have specific characteristic is used. The data research focused on the teacher’s speech acts in Wisma Bahasa Yogyakarta who teach Indonesian in natural speech. In line with the research goal, the result of this study show that the kinds of speech acts is devided into six categories, those are (a) assertive speech acts, (b) hesitative speech acts, (c) directive speech acts, (d) expressive speech acts, (e) comissive speech acts, and (f) declarative speech acts. Assertive speech acts is marked with the using of proposition which indicate of speaker conviction in his utterance. Hesitative speech acts is marked with the using of proposition which indicate the speaker unbelieveable in his utterance. Directive speech acts is classified into two terms, those are to express believeable and also unbelieveable proposition in his utterance can do by the speaker. Expressive speech acts is classified into two terms, those are to express evaluation, directly or indirectly. Comissive speech act is classified into two terms, those are to express that the listener has believeable and also unbelieveable to do what is said in his utterance. Declarative speech acts is classified into three terms, those are to express that the speaker give permission, forbiden, and give limitation. Hesitative speech act in this study have not been embodied in the classification of types of speech according to Searle, whereas hesitatif speech act is not something impossible in a speech. Sometimes speaker not have conviction of truth utterance.